The effect of non-root fertilizing on the yield and quality of plum fruits of the Velikaya sinyaya variety in arid conditions of the Northern Precaspian Sea - T. I. Alexandrova (Аграрная наука Евро-Северо-Востока, 2024)
The research was carried out in order to study the effect of non-root fertilizing using complex fertilizers on the yield and quality of plum fruits of the Velikaya sinyaya variety in the Astrakhan region. The following treatment variants with complex fertilizers were used in the experiment: Master; Aquarin; Ultramag Boron + Ultramag Calcium; Aquarin + Ultramag Boron + Ultramag Calcium. Non-root fertilizing of plum plants was carried out before flowering, after flowering and during fruit development. On average for 2021-2023 non-root treatments contributed to an increase in the number of plum ovaries compared with the control (water treatment) by 3.3...26.7 %, the best result was obtained in the variant Ultramag Boron + Ultramag Calcium. In all variants of the experiment, foliar fertilization increased the yield of plum of the Velikaya sinyaya variety by 3.1...4.2 t/ha (LSD05 = 0.1 t/ha). The highest yield of plum fruits was formed in the variant Aquarin + Ultramag Boron + Ultramag Calcium – 12.9 t/ha (in the control – 8.7 t/ha). The maximum values of the average fruit weight were obtained in the variants Ultramag Boron + Ultramag Calcium and Aquarin + Ultramag Boron + Ultramag Calcium – 45.1 and 45.6 g, respectively (in the control – 43.3 g, LSD05 = 1.2 g). Foliar fertilizing with Ultramag Boron fertilizers together with Ultramag Calcium provided a higher sugar content (14.2 %) and the value of the sugar acid index (17.7) in the fruits of the Velikaya sinyaya plum variety (at the control – 13.2 % and 16.5 respectively).